2016
DOI: 10.4174/astr.2016.90.3.157
|View full text |Cite
|
Sign up to set email alerts
|

Duodenal stump fistula after gastrectomy for gastric cancer: risk factors, prevention, and management

Abstract: PurposeA duodenal stump fistula is one of the most severe complications after gastrectomy for gastric cancer. We aimed to analyze the risk factors for this problem, and to identify the methods used for its prevention and management.MethodsWe retrospectively reviewed the clinical data of 716 consecutive patients who underwent curative gastrectomy with a duodenal stump for gastric cancer between 2008 and 2013.ResultsA duodenal stump fistula occurred in 16 patients (2.2%) and there were 2 deaths in this group. Un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
31
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(36 citation statements)
references
References 18 publications
5
31
0
Order By: Relevance
“…DSL has several causes, as noted above. Paik et al reported that gastric outlet obstruction before surgery was a significant risk factor for DSL due to inflammation of the surrounding duodenal wall tissue [9]. In addition, the staple line itself in patients requiring re-operation was actually intact in our study.…”
Section: Discussionsupporting
confidence: 55%
“…DSL has several causes, as noted above. Paik et al reported that gastric outlet obstruction before surgery was a significant risk factor for DSL due to inflammation of the surrounding duodenal wall tissue [9]. In addition, the staple line itself in patients requiring re-operation was actually intact in our study.…”
Section: Discussionsupporting
confidence: 55%
“…Our study highlighted 114 cases of early complications after radical gastrectomy ( concluded that preoperative multiple comorbidity was the main reason of postoperative duodenal stump stula. 17 ; 3. In the past, the stump was only reinforced, but not embedded.…”
Section: Discussionmentioning
confidence: 99%
“…Some surgeons applied fibrinsealant (Greenplasty, Green Cross Corp., Seoul, Korea) or absorbable reinforcement felt (Neoveil, Gunze Ltd., Kyoto, Japan) at staple-line of duodenal stump to prevent the DSF. However, its clinical efficacy remains unclear [ 2 ].…”
Section: Discussionmentioning
confidence: 99%
“…The overall incidence of duodenal stump fistula (DSF) or duodenal stump leakage is reportedly between 1.6% to 5% and is one of the most serious complications of BillrothII or Roux en Y reconstruction after gastrectomy for gastric cancer [ 1 2 ]. Several investigators presented their clinical experience, such as the clinical course and the pertinent management of DSF [ 3 4 ].…”
Section: Introductionmentioning
confidence: 99%